2007
DOI: 10.1590/s0044-59672007000100002
|View full text |Cite
|
Sign up to set email alerts
|

Cross-scale determinants of palm species distribution

Abstract: We investigate palm species distribution, richness and abundance along the Mokoti, a seasonally-dry river of southeastern Amazon and compare it to the patterns observed at a large scale, comprising the entire Brazilian territory. A total of 694 palms belonging to 10 species were sampled at the Mokoti River basin. Although the species showed diverse distribution patterns, we found that local palm abundance, richness and tree basal area were significantly higher from the hills to the bottomlands of the study reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 26 publications
6
37
0
5
Order By: Relevance
“…Indeed, the difference in altitude measured by Scariot et al (1989) in the Tocantins valley was also substantially shorter than the difference that we found in the 51 st BIS forest. The palm E. oleracea was rare in the study by Kahn (1987), and was not found in the other studied site southward in the Xingu basin (Salm et al 2007), where it is replaced by Euterpe precatoria.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…Indeed, the difference in altitude measured by Scariot et al (1989) in the Tocantins valley was also substantially shorter than the difference that we found in the 51 st BIS forest. The palm E. oleracea was rare in the study by Kahn (1987), and was not found in the other studied site southward in the Xingu basin (Salm et al 2007), where it is replaced by Euterpe precatoria.…”
Section: Discussionmentioning
confidence: 54%
“…Attalea phalerata, the next species in our rank of association was not documented in any of the three other nearest study sites (Kahn 1987;Scariot et al 1989;Salm et al 2007), despite its wide distribution in the southern limits of the Amazon (Henderson et al 1995). It is very abundant in the Pantanal-Matogrossense, the world's largest floodplain, where it occurs in both alluvial and periodically flooded soils, and islands of woody vegetation a few meters above the floodable areas (Henderson et al 1995).…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations